Hydroborane / polyrotaxane composite interfacial film modified metal zinc negative electrode as well as preparation method and application thereof

By modifying the anode using borophene/polyrotaxane composite interface film on the anode of the aqueous zinc ion battery, the problems of dendrite growth, hydrogen evolution, corrosion and passivation were solved, and the stability and reversibility of the zinc anode were significantly improved. Extended cycle life and improved Coulombic efficiency.

CN119340517APending Publication Date: 2025-01-21ZHENGZHOU UNIVERSITY OF LIGHT INDUSTRY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411470130.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The negative electrode of the aqueous zinc ion battery has side reaction problems such as dendrite growth, hydrogen evolution, corrosion and passivation, which leads to poor stability and reversibility, hindering the commercialization process and large-scale application of the battery.

Method used

The metal zinc negative electrode metal zinc is used with hydrogenated totohyl/polymer composite meal mask. Through the in-situ surface of the metal zinc surface of the inorganic-organic composite interface, it forms an excellent mechanical strength and rich zinc site. Direct contact with metal zinc regulates zinc ions uniformly.

Benefits of technology

Significantly inhibits the uncontrollable growth of zinc dendrites, reduces side reactions such as hydrogen evolution, corrosion and passivation, improves the reversibility and stability of the zinc anode, extends cycle life and improves Coulombic efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340517A_ABST
    Figure CN119340517A_ABST
Patent Text Reader

Abstract

The invention relates to a boron hydride alkene / polyrotaxane composite interfacial film modified metal zinc negative electrode and a preparation method and application thereof, and belongs to the technical field of aqueous zinc ion battery negative electrode materials. The modified metal zinc negative electrode is composed of metal zinc and an inorganic-organic composite gel polymer interfacial film formed on the surface of the metal zinc through crosslinking of borohydride, polyrotaxane and polyacrylamide. The thickness of the interfacial film is 1-1000 [mu] m, and the interfacial film is uniformly modified on the surface of metal zinc through in-situ free radical polymerization. The inorganic-organic composite interfacial film has excellent mechanical strength, rich zinc-loving sites and relatively high ionic conductivity, and can also block direct contact between aqueous electrolyte and metal zinc, so that zinc dendrite growth and interface side reactions such as hydrogen evolution, corrosion and passivation can be effectively relieved. The interfacial film can significantly enhance the reversibility and cycling stability of the zinc negative electrode, the preparation process is simple and efficient, the operability is strong, and the method is green and safe, and is of great importance to the realization of an environment-friendly and sustainable aqueous zinc ion battery technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of negative electrode materials for aqueous zinc ion batteries, and in particular to a borohydride / polyrotaxane composite interface film modified metal zinc negative electrode and a preparation method and application thereof. Background Art

[0002] With the rapid development of modern society, the increasing demand for energy is driving the development of highly safe, high-performance, low-cost and environmentally friendly electrochemical energy storage technologies. Among the many secondary battery systems, aqueous zinc-ion batteries have the characteristics of high safety, high theoretical specific capacity (820mAh / g) and green environmental protection. In addition, the metal zinc reserves that can be directly used as the negative electrode are abundant and low in cost. Therefore, they are considered to be the ideal choice for the next generation of large-scale energy storage technology. However, the occurrence of side reactions such as uncontrollable growth of zinc dendrites, hydrogen evolution and corrosion significantly reduces the stability and reversibility of the zinc negative electrode, which seriously hinders the commercialization process and large-scale application of aqueous zinc-ion batteries. Therefore, it is crucial to modify the zinc negative electrode to improve the overall performance of aqueous zinc-ion batteries.

[0003] In recent years, research on improving the performance of zinc anodes has mainly focused on zinc anode interface modification, structural design of new zinc anodes, electrolyte optimization, and the development of new separators. The zinc anode / electrolyte interface is an important place for the combination and separation of electrons and ions and the transfer of charges during electrochemical reactions. The zinc deposition behavior is closely related to the properties of the zinc anode / electrolyte interface. Therefore, constructing an interface protection layer between the metal zinc anode and the electrolyte has the advantages of simplicity and high practical value. Organic polymers have rich functional groups that can interact with zinc ions, promote uniform deposition of zinc ions, and improve cycle stability. However, the interfacial compatibility of polymer interface films with zinc anodes is poor, which will reduce battery performance under long-term operation or deep charge and discharge conditions. Inorganic materials usually have the advantages of high shear modulus, corrosion resistance, structural stability, and high ionic conductivity, but they are brittle. In comparison, inorganic-organic composite interface films can combine the advantages of the above two, overcome the limitations of single materials, and achieve synergistic enhancement effects between multiple components. The two-dimensional nanosheet structure of hydride borophylene coupled with the dynamic sliding ring cross-linking network of polyrotaxane is conducive to leveling the distribution of zinc ion flow and promoting the directional and rapid migration of ions at the zinc negative electrode interface, thereby inhibiting the uncontrollable growth of zinc dendrites. This inorganic-organic composite interface film can also block the direct contact between aqueous electrolyte and metallic zinc, and can effectively slow down the interfacial side reactions such as hydrogen separation, corrosion and passivation, thereby improving the reversibility and stability of the zinc negative electrode, which will be of great significance to promote the development and application of aqueous zinc-ion batteries. Summary of the invention

[0004] The present invention aims to provide a metal zinc negative electrode modified by a hydride borophylene / polyrotaxane composite interface film and a preparation method and application thereof, so as to solve the problems of dendrite growth, hydrogen evolution, corrosion and passivation commonly existing in the negative electrode of aqueous zinc ion batteries.

[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0006] A hydridoborophene / polyrotaxane composite interface film modified metal zinc negative electrode, the negative electrode material is composed of metal zinc and an inorganic-organic composite gel polymer interface film on the surface of which is formed by cross-linking hydridoborophene (HB), polyrotaxane (PR) and polyacrylamide (PAM).

[0007] Furthermore, the composite film has a thickness of 1 to 1000 μm; the metal zinc substrate is zinc foil or zinc alloy foil, and has a thickness of 10 to 100 μm.

[0008] The method for preparing the metal zinc negative electrode modified by the hydride borophylene / polyrotaxane composite interface film of the present invention specifically comprises the following steps:

[0009] (1) Cyclodextrin (CD) was used as the main cyclic molecule and chain molecule polyethylene glycol (PEG) was used as the guest molecule axis. The PR supramolecular solution was obtained by self-assembly through host-guest interaction after being dissolved in deionized water.

[0010] (2) adding HB nanosheets to the PR solution and mixing them evenly to obtain a HB / PR mixed solution;

[0011] (3) dissolving the monomer acrylamide, the initiator potassium persulfate and the cross-linking agent N'N-methylenebisacrylamide in a zinc salt solution, and then adding them to the HB / PR mixed solution, and mixing them thoroughly to obtain a zinc negative electrode interface film precursor solution;

[0012] (4) Taking an appropriate amount of zinc negative electrode interface film precursor solution, evenly dripping it on the surface of the metal zinc negative electrode sheet, placing it in a vacuum oven for in-situ polymerization, and obtaining the zinc negative electrode material.

[0013] Furthermore, in step (1), the cyclodextrin is α-CD, β-CD or γ-CD, and the concentration of cyclodextrin is 50-500 mg / mL; the molecular weight of polyethylene glycol is 500-50000, and the concentration of polyethylene glycol is 5-100 mg / mL.

[0014] Furthermore, the concentration of the borohydride nanosheets in step (2) is 0.5 to 10 mg / mL.

[0015] Furthermore, in the zinc negative electrode interface film precursor solution of step (3), the concentration of acrylamide is 50-100 mg / mL, the concentration of potassium persulfate is 0.2-1 mg / mL, the concentration of N'N-methylenebisacrylamide is 0.5-1.5 mg / mL, and the concentration of zinc salt is 1-3 mol / L; the zinc salt is one or more of zinc sulfate, zinc chloride, zinc acetate, zinc nitrate, zinc fluoride, zinc trifluoromethanesulfonate, and zinc bis(trifluoromethylsulfonyl)imide.

[0016] Furthermore, in step (4), the amount of the zinc negative electrode interface film precursor solution is 30 to 100 μL; the polymerization temperature is 45 to 65° C., and the polymerization time is 0.2 to 0.5 h; and the diameter of the electrode sheet is 10 to 20 mm.

[0017] The present invention also provides an application of a metal zinc negative electrode modified by a hydride borophylene / polyrotaxane composite interface film, which is applied to assembling an aqueous zinc ion battery.

[0018] Advantages and beneficial effects of the present invention:

[0019] 1. The present invention generates a uniform interfacial film in situ at the interface of the metal zinc negative electrode, which has excellent mechanical strength, abundant zinc-philic sites and high ionic conductivity. It utilizes the inorganic-organic synergistic enhancement effect to regulate the uniform deposition and nucleation of zinc ions, effectively improving the dendrite problem of the zinc negative electrode.

[0020] 2. The interfacial film constructed in situ at the metal zinc negative electrode interface of the present invention can block the direct contact between the aqueous electrolyte and the metal zinc. At the same time, the abundant zinc-philic sites can promote the desolvation process of zinc ions, thereby effectively reducing competitive side reactions such as the electrolyte / negative electrode interface, thereby improving the reversibility and stability of the zinc negative electrode.

[0021] 3. The hydride borophylene / polyrotaxane composite interface film provided by the present invention is constructed by in situ free radical polymerization, and has the advantages of simple operation, low cost, green and safe, and has high compatibility with the zinc negative electrode interface, easy to scale up production and industrial application, which is crucial to achieving environmentally friendly and sustainable aqueous zinc ion battery technology, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The surface morphology SEM images of the zinc negative electrodes prepared in Comparative Example 1 and Examples 1 to 5 after constant current electrodeposition;

[0023] Figure 2 The linear sweep voltammetry curves of the zinc negative electrodes prepared in Comparative Example 1 and Examples 1 to 5;

[0024] Figure 3 The Tafel curves of the zinc negative electrodes prepared in Comparative Example 1 and Example 2;

[0025] Figure 4 The time-voltage curve of the zinc / zinc symmetric battery assembled using the zinc negative electrodes prepared in Comparative Example 1 and Example 2;

[0026] Figure 5 The coulombic efficiency of zinc / copper asymmetric cells assembled using the zinc negative electrodes prepared in Comparative Example 1 and Example 2. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but the embodiments of the present invention are not limited thereto. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] A metal zinc negative electrode modified by a hydride borophylene / polyrotaxane composite interface film, wherein the negative electrode material is composed of metal zinc and an inorganic-organic composite gel polymer interface film formed by cross-linking hydride borophylene (HB), polyrotaxane (PR) and polyacrylamide (PAM) on its surface, and the preparation process specifically comprises the following steps:

[0030] (1) At a constant temperature of 45°C, 600 mg of α-cyclodextrin (α-CD) and 45 mg of ethylene glycol (PEG1000, molecular weight M w 1000) was dissolved in 3 mL of deionized water, the α-CD concentration was 200 mg / mL, the PEG concentration was 15 mg / mL, and the mixture was fully mixed and stirred for 0.5 h to obtain a PR supramolecular solution;

[0031] (2) 9 mg of HB nanosheets and 3 mL of PR supramolecular solution were mixed and stirred for 0.5 h to obtain a HB / PR mixed solution in which the HB concentration was 3 mg / mL;

[0032] (3) 6.32 g ZnSO4·7H2O was dissolved in 8 mL deionized water to obtain a ZnSO4 aqueous solution, and then 800 mg acrylamide powder, 6.4 mg potassium persulfate and 8.0 mg N,N'-methylenebisacrylamide were added, and the mixture was stirred for 0.5 h at 4 °C to disperse evenly, and then mixed with 3 mL HB / PR solution to obtain a zinc negative electrode interface film precursor solution, wherein the concentration of acrylamide was 72.7 mg / mL, the concentration of potassium persulfate was 0.582 mg / mL, and the concentration of N'N-methylenebisacrylamide was 0.728 mg / mL;

[0033] (4) Take 50 μL of zinc negative electrode interface film precursor solution, evenly drop it on the surface of the metal zinc negative electrode sheet, place it in a vacuum oven at 60°C for in-situ polymerization for 0.25 h, and obtain a hydride boryne / polyrotaxane composite interface film modified metal zinc negative electrode. The thickness of the composite film is 300 μm, with a metal zinc foil as the substrate, the thickness is 0.05 mm, and the diameter is 12 mm.

[0034] Embodiments 2 to 5

[0035] In Examples 2 to 5, except that the components of the zinc negative electrode interface film precursor solution are prepared as shown in Table 1, the rest of the experimental process is the same as that of Example 1.

[0036] Table 1 Compositions of the zinc negative electrode interface film precursor solutions prepared in Examples 1 to 5

[0037] Examples Cyclodextrin Types Types of Ethylene Glycol Borene HB concentration Zinc salt concentration and type Example 1 α-CD PEG1000 3mg / mL <![CDATA[2mol / L ZnSO4]]> Example 2 α-CD PEG2000 3mg / mL <![CDATA[2mol / L ZnSO4]]> Example 3 α-CD PEG3500 3mg / mL <![CDATA[2mol / L ZnSO4]]> Example 4 β-CD PEG2000 3mg / mL <![CDATA[2mol / L ZnSO4]]> Example 5 γ-CD PEG2000 3mg / mL <![CDATA[2mol / L ZnSO4]]>

[0038] Comparative Example 1

[0039] The metal zinc foil without modified interface film is directly hammered to obtain the negative electrode sheet, which has a thickness of 0.05 mm and a diameter of 12 mm.

[0040] Comparative Examples 2 to 4

[0041] In Comparative Examples 2 to 4, except that the components of the zinc negative electrode interface film precursor solution were prepared as shown in Table 2, the rest of the experimental process was the same as that of Example 1.

[0042] Table 2 Components of the zinc negative electrode interface film precursor solution prepared in Comparative Examples 2 to 4

[0043] Examples Cyclodextrin Types Types of Ethylene Glycol Borene hydride concentration Zinc salt concentration and type Comparative Example 2 - - - <![CDATA[2mol / L ZnSO4]]> Comparative Example 3 - - 3mg / mL <![CDATA[2mol / L ZnSO4]]> Comparative Example 4 α-CD PEG2000 - <![CDATA[2mol / L ZnSO4]]>

[0044] Test Example 1

[0045] Observation of the surface dendrite growth of the zinc negative electrodes prepared in Comparative Example 1 and Examples 1 to 5 by constant current electrodeposition.

[0046] The zinc negative electrodes prepared in Comparative Example 1 and Examples 1 to 5 were used to assemble a zinc / zinc symmetrical battery. The battery was deposited at a constant current for 20 h using a battery tester at room temperature. The current density was set to 1 mA / cm 2 The morphology of zinc deposition was observed by scanning electron microscopy (SEM) at an accelerating voltage of 15 kV. Figure 1 shown.

[0047] Depend on Figure 1 Analysis shows that a large number of blocky dendrites appear on the surface of the zinc negative electrode with unmodified interface (Comparative Example 1), and the dendrite growth on the surface of the zinc negative electrode with modified interface film (Examples 1 to 5) is significantly inhibited, and the improvement effect of Examples 2 and 5 is the most significant.

[0048] Test Example 2

[0049] The hydrogen evolution behavior of the zinc negative electrodes prepared in Comparative Example 1 and Examples 1 to 5 was tested.

[0050] First, the zinc negative electrode prepared in Comparative Example 1 and Examples 1 to 5 was used as the reference electrode, commercial titanium foil (60 μm thick) was used as the working electrode, the electrolyte was a 2 mol / L ZnSO4 aqueous solution, and the separator was filter paper to assemble a zinc / titanium asymmetric cell. Then, the hydrogen evolution behavior during zinc deposition was characterized by linear sweep voltammetry with an electrochemical workstation at a sweep rate of 1 mV / s. The results are shown in FIG. Figure 2 shown.

[0051] Depend on Figure 2 Analysis shows that compared with the zinc negative electrode without modified interface film (Comparative Example 1), the hydrogen evolution behavior of the zinc negative electrode modified by the interface film (Examples 1 to 5) all shows obvious polarization phenomenon, and the polarization phenomenon of the hydrogen evolution reaction of the zinc negative electrode prepared in Example 2 is the most obvious, indicating that the zinc negative electrode modified by the interface film can significantly inhibit the hydrogen evolution side reaction.

[0052] Test Example 3

[0053] The corrosion resistance of the zinc negative electrodes prepared in Comparative Example 1 and Example 2 was tested.

[0054] First, the zinc negative electrodes prepared in Comparative Example 1 and Example 2 were used to assemble a zinc / zinc symmetrical battery, wherein the electrolyte was a 2 mol / L ZnSO4 aqueous solution and the separator was a filter paper. Then, the corrosion current density of the zinc electrode in the electrolyte was tested using an electrochemical workstation at a scan rate of 10 mV / s. The results are shown in FIG. Figure 3 shown.

[0055] Depend on Figure 3 Analysis shows that compared with the zinc negative electrode without modified interface film (Comparative Example 1), the corrosion current density of the zinc negative electrode prepared in Example 2 is significantly reduced, indicating that the interface film modified zinc negative electrode can significantly inhibit corrosion side reactions.

[0056] Test Example 4

[0057] The zinc / zinc symmetrical batteries assembled with the zinc negative electrodes prepared in Comparative Examples 1 to 4 and Example 2 were subjected to a cycle stability test.

[0058] First, the zinc negative electrodes prepared in Comparative Example 1 and Example 2 were used to assemble a zinc / zinc symmetrical battery, wherein the electrolyte was a 2 mol / L ZnSO4 aqueous solution and the separator was a filter paper. Then, a constant current charge-discharge cycle test was performed using a battery tester at a constant temperature of 25°C, with a current density of 1 mA / cm 2 , deposition / stripping surface capacity is 1 mAh / cm 2 , the cycle stability is as follows Figure 4 shown.

[0059] Depend on Figure 4 The analysis shows that the Zn / Zn symmetric battery assembled with the zinc negative electrode prepared in Comparative Examples 1 to 4 has a high conductivity at 1 mA / cm 2 , 1mAh / cm 2 Under the test conditions, short circuit phenomenon occurred after cycling for 228h, 313h, 505h and 565h respectively, while the Zn / Zn symmetric battery assembled with the zinc negative electrode prepared in Example 2 could be stably cycled for 1000h, indicating that such an interface film can significantly improve the cycle stability of the zinc negative electrode.

[0060] Test Example 5

[0061] The coulombic efficiency test was carried out on the zinc / copper asymmetric battery assembled with the zinc negative electrode prepared in Comparative Example 1 and Example 2.

[0062] First, a zinc / copper asymmetric battery was assembled using the zinc negative electrode prepared in Comparative Example 1 and Example 2, with commercial copper foil as the positive electrode, 2 mol / L ZnSO4 aqueous solution as the electrolyte, and filter paper as the separator. Then, a constant current charge-discharge cycle test was performed using a battery tester at a constant temperature of 25°C, with a current density of 1 mA / cm 2 , the deposition surface capacity is 1 mAh / cm 2 , the stripping cut-off voltage is 0.5V vs.Zn 2+ / Zn, the results are as follows Figure 5 shown.

[0063] Depend on Figure 5 The analysis shows that the coulombic efficiency of the zinc negative electrode prepared in Comparative Example 1 is 1 mA / cm 2 , 1mAh / cm 2 Obvious fluctuations occurred during the cycle under the test conditions, while the coulombic efficiency of the zinc negative electrode prepared in Example 2 could be stably cycled for 200 cycles, indicating that the reversibility of zinc deposition / stripping was significantly improved after the negative electrode was modified.

[0064] The present invention modifies a hydride borophylene / polyrotaxane composite interface film on the surface of metallic zinc by in-situ free radical polymerization. The inorganic-organic composite interface film has excellent mechanical strength, abundant zinc-philic sites and high ionic conductivity, and can also block the direct contact between aqueous electrolyte and metallic zinc, thereby effectively alleviating zinc dendrite growth and interfacial side reactions such as hydrogen evolution, corrosion and passivation. Therefore, the interface film can significantly enhance the cycle life and coulomb efficiency of the zinc negative electrode. In addition, the interface film of the present invention has the advantages of simple and efficient preparation process, strong operability and green safety, and has good application prospects in the field of aqueous zinc ion batteries.

[0065] In summary, the above embodiments are only for explaining the relevant principles and implementation methods, and are intended to enable people familiar with the technology to understand the content of the present invention and implement it accordingly, and are not intended to limit the present invention. Any modification, equivalent replacement, improvement, etc. made to the present invention without departing from the principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A metal zinc negative electrode modified by a hydride borophylene / polyrotaxane composite interface film, characterized in that: The modified metal zinc negative electrode consists of a metal zinc substrate and an inorganic-organic composite gel polymer interface film on its surface, wherein the inorganic-organic composite gel polymer interface film is formed by cross-linking borohydride (HB), polyrotaxane (PR) and polyacrylamide (PAM).

2. The metal zinc negative electrode modified by the hydride borophylene / polyrotaxane composite interface film according to claim 1, characterized in that: The thickness of the inorganic-organic composite gel polymer interface film is 1-1000 μm; the metal zinc substrate is zinc foil or zinc alloy foil, and the thickness of the metal zinc substrate is 10-100 μm.

3. The method for preparing a metal zinc negative electrode modified by a hydride borophylene / polyrotaxane composite interface film according to claim 1 or 2, characterized in that: The specific steps include: (1) Cyclodextrin (CD) and chain molecule polyethylene glycol (PEG) are dissolved in deionized water, and cyclodextrin is used as the main ring molecule and chain molecule polyethylene glycol is used as the guest molecule axis to obtain PR supramolecular solution by self-assembly through host-guest interaction; (2) adding HB nanosheets to the PR supramolecular solution and mixing them evenly to obtain a HB / PR mixed solution; (3) dissolving the monomer acrylamide, the initiator potassium persulfate and the cross-linking agent N'N-methylenebisacrylamide in a zinc salt solution, and then adding them to the HB / PR mixed solution, and mixing them thoroughly to obtain a zinc negative electrode interface film precursor solution; (4) taking an appropriate amount of zinc negative electrode interface film precursor solution, evenly drop-coating it on the surface of the metal zinc negative electrode sheet, placing it in a vacuum oven for in-situ polymerization, and obtaining the hydride borophylene / polyrotaxane composite interface film modified metal zinc negative electrode.

4. The method for preparing the metal zinc negative electrode modified by the hydride borophylene / polyrotaxane composite interface film according to claim 2, characterized in that: In step (1), the cyclodextrin is α-CD, β-CD or γ-CD, and the concentration of cyclodextrin is 50-500 mg / mL; the molecular weight of polyethylene glycol is 500-50000, and the concentration of polyethylene glycol is 5-100 mg / mL.

5. The method for preparing the metal zinc negative electrode modified by the hydride borophylene / polyrotaxane composite interface film according to claim 2, characterized in that: The concentration of the borohydride nanosheets in the HB / PR mixed solution in step (2) is 0.5-10 mg / mL.

6. The method for preparing the metal zinc negative electrode modified by the hydride borophylene / polyrotaxane composite interface film according to claim 2, characterized in that: In step (3), the concentration of acrylamide in the zinc negative electrode interface film precursor solution is 50-100 mg / mL, the concentration of potassium persulfate is 0.2-1 mg / mL, the concentration of N'N-methylenebisacrylamide is 0.5-1.5 mg / mL, and the concentration of zinc salt is 1-3 mol / L; the zinc salt is one or more of zinc sulfate, zinc chloride, zinc acetate, zinc nitrate, zinc fluoride, zinc trifluoromethanesulfonate, and zinc bis(trifluoromethylsulfonyl)imide.

7. The method for preparing a metal zinc negative electrode modified by a hydride borophylene / polyrotaxane composite interface film according to claim 2, characterized in that: The polymerization temperature in step (4) is 45-65° C., and the polymerization time is 0.2-0.5 h.

8. The method for preparing the metal zinc negative electrode modified by the hydride borophylene / polyrotaxane composite interface film according to claim 2, characterized in that: The amount of the zinc negative electrode interface film precursor solution in step (4) is 30 to 100 μL, and the diameter of the electrode sheet is 10 to 20 mm.

9. An application of a metal zinc negative electrode modified by a hydride borophylene / polyrotaxane composite interface film prepared by the method according to any one of claims 3 to 8, characterized in that: Used to assemble aqueous zinc-ion batteries.

Citation Information

Cited By

  • Wide-temperature-range polymer solid-state zinc secondary battery as well as preparation method and application thereof

    CN120319906A